CTNI-42. FIRST-IN-HUMAN FLUORESCENCE GUIDED SURGERY OF HIGH-GRADE GLIOMAS USING PANITUMUMAB-IRDYE800. (9th November 2020) - Zhou, Quan; van den Berg, Nynke; Nishio, Naoki; Lu, Guolan; Chirita, Stefania; Raymundo, Roan; Yi, Grace; Vogel, Hannes; Cayrol, Romain; Rosenthal, Eben; Li, Gordon
Abstract: INTRODUCTION: High-grade gliomas (HGGs) are malignant brain tumors with devastating prognosis. Extent of resection predicts survival in patients, but current neuroimaging approaches lack tumor specificity. The epidermal growth factor receptor (EGFR) is a biomarker heterogeneously expressed in HGGs. We assessed the feasibility of imaging HGGs using a near-infrared fluorescent anti-EGFR antibody. METHODS: Nine patients with contrast enhancing HGGs on presurgical MRI scan were systemically infused with a flat dose of either 50mg (n = 4) or 100mg (n = 5) panitumumab-IRDye800, 1–5 days before surgery. Near-infrared fluorescence imaging of tumor and histologically normal brain tissues was performed intraoperatively and ex vivo. Fluorescence was measured as mean fluorescence intensity (MFI), and tumor-to-background ratio (TBR) were calculated by comparing MFIs of tumor and histologically uninvolved tissue. Immunohistopathological staining of EGFR was performed on formalin fixed paraffin embedded tissue sections. RESULTS: Both MFI and TBR were positively correlated to panitumumab-IRDye800 dose per body weight (R 2 = 0.59 and 0.07, P < 0.0001 and P = 0.046 respectively). The TBR was higher at a 100 mg dose than at 50 mg (2.1 vs. 1.5). The smallest detectable tumor volume in a closed-field setting was 21 mg with 50 mg of dye and 12 mg with 100 mg. On sections of paraffin embedded tissues, positive EGFR protein expression was observed in 88.9% ± 12.4% of tumor tissues and positively correlated with fluorescence. Sensitivity and specificity of tumor fluorescence for viable tumor detection was calculated and fluorescence was found to be highly sensitive (93%) and specific (81%) for viable tumor tissues while normal brain tissues showed minimal fluorescence. No adverse events related to the imaging probe was observed. CONCLUSION: This first-in-human study demonstrates the feasibility and safety of antibody based imaging for contrast enhancing high-grade gliomas.